2017
DOI: 10.5194/angeo-35-547-2017
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variability in MLT turbulence inferred from in situ and ground-based observations during the WADIS-1 sounding rocket campaign

Abstract: Abstract. In summer 2013 the WADIS-1 sounding rocket campaign was conducted at the Andøya Space Center (ACS) in northern Norway (69 • N, 16 • E). Among other things, it addressed the question of the variability in mesosphere/lower thermosphere (MLT) turbulence, both in time and space. A unique feature of the WADIS project was multi-point turbulence sounding applying different measurement techniques including rocket-borne ionization gauges, VHF MAARSY radar, and VHF EISCAT radar near Tromsø. This allowed for ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 71 publications
2
27
0
Order By: Relevance
“…During the WADIS sounding rocket campaign in 2013 (Strelnikov et al, 2014), there were 14 launches of balloon-borne radiosondes (model: MarkIIa DGPS (LOS), (p/n 1648-611)) at the radar site of MAARSY. The ascent rate of the radiosondes (RS) used in this study was roughly 5 m s −1 .…”
Section: Derivation Of ε From Radiosonde Datamentioning
confidence: 99%
See 1 more Smart Citation
“…During the WADIS sounding rocket campaign in 2013 (Strelnikov et al, 2014), there were 14 launches of balloon-borne radiosondes (model: MarkIIa DGPS (LOS), (p/n 1648-611)) at the radar site of MAARSY. The ascent rate of the radiosondes (RS) used in this study was roughly 5 m s −1 .…”
Section: Derivation Of ε From Radiosonde Datamentioning
confidence: 99%
“…In this study, we compare radar-based estimates of ε (based on the Middle Atmosphere Alomar Radar SYstem -MAARSY -spectral width data) with radiosonde data applying a so-called Thorpe analysis (Thorpe, 1977;Clayson and Kantha, 2008;Wilson et al, 2011). These radiosonde measurements were obtained during the WADIS sounding rocket campaign in 2013 as described in Strelnikov et al (2014). We are hence able to validate the radar estimates of turbulence by comparing them with the simultaneous in situ measurements with radiosondes.…”
Section: Introductionmentioning
confidence: 99%
“…The main goal of the mission was to study propagation of gravity waves (GWs) from their sources in the troposphere to their level of dissipation in the MLT and quantification of their contribution to the energy budget of the MLT. For an overview of the WADIS project and its main mission the reader is referred to Strelnikov et al (2017).…”
Section: Experiments Descriptionmentioning
confidence: 99%
“…Experimental studies with rocket borne ionization gauges have shown that small-scale turbulence is present in the very stable inversion layer, and in some cases, indicates mixing in the quasiadiabatic layer above the inversion (Lehmacher and Lübken, 1995;Lehmacher et al, 2006Lehmacher et al, , 2011Szewczyk et al, 2013;Strelnikov et al, 2017). Since rocket measurements of neutral turbulence are relatively complex and costly, they often only provide a single profile of temperature and turbulence, while model results allow the analysis in the full spatialtemporal domain.…”
Section: Introductionmentioning
confidence: 99%